Cultural Proximity of Korean and Indonesian in Korean Dramas - Suzy Azeharie (WACANA: Jurnal Ilmiah Ilmu Komunikasi, 2023)
This paper, which is a narrative analysis, seeks to explore why Korean drama as a form of hallyu cultural product is favoured by the Indonesian people by using the cultural proximity theory from Joseph Straubhaar. According to this theory the audience will prefer products of their own culture or the same as their culture. This research approach is a qualitative research with narrative analysis method. Audiences will prefer the same production because of elements such as star appeal, local knowledge, topics, issues, the environment, and the ethnicity of people in the media. The author discusses five cultural similarities between the two countries, namely the same history, family relationships based on extended family, language and social norms, family lineage and culinary. The results showed that the historical similarities between Korea and Indonesia which had been colonized by Japan, extended family forms in Indonesian and Korean families, respect for parents and manners of behaviour between Indonesians and Koreans and the same food, namely making rice and side dishes as staple foods made Korean dramas liked by the Indonesian people.